Shifting perceptions of black students in a South African university residence - Vandeyar, S.; Mohale, A. (South African Journal of Higher Education, 2017)
Utilising the methodology of portraiture this qualitative case study set out to understand how students from different racial and ethnic backgrounds interpret their own experiences as they shared their personal space in a university residence with people who had previously been seen as the out-group. Data capture included semi-structured interviews, observations, and field notes. Theoretical moorings of this study were critical race theory and contact theory. Data was analysed by means of content analysis. Findings of this study reveal that contact between diverse students helped to reduce prejudices thus changing pre-conceived student perceptions.